(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Elena Ionescu examines Momos, the Greek deity of mockery and sarcasm. Unlike other gods, Momos embodies harsh criticism and frankness, often bridging the divine and mortal realms. The study traces his presence from Hesiod and Aesop’s fables to Lucian of Samosata’s satirical dialogues. Momos exposes the imperfections of divine creations and challenges the gods' authority through wit. Ultimately, the author portrays him as an educational force using laughter to reveal uncomfortable truths and human failings. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.